Analysis of Voltage Drop Improvement Using Transformer Insertion Method in LG-02 Receiver Lhokseumawe City - Prastia, Ramadhan; Asran, Asran; Hasibuan, Arnawan; Rosdiana, Rosdiana; Ezwarsyah, Ezwarsyah (MSD Institute, 2024)
The LG-02 Darussalam distribution network, within the operational area of PT. PLN (Persero) ULP Lhokseumawe City, shows low voltage issues at the Gg. Damai and Bakso Pakde substations. According to PT. PLN standards, transformers face adverse loading conditions if usage exceeds 80% capacity. Specifically, Gg. Damai operates at 88.5% capacity and Bakso Pakde at 94.4%, resulting in a voltage drop of 370 Volts from the nominal 400 Volts at end consumer service phases. SPLN T6.001-2013 recommends that voltage differences at supply terminals not exceed ±10% of the system's nominal voltage, allowing a maximum drop of 360 Volts between phases under normal conditions. Failure to address these issues promptly risks further significant voltage drops. To resolve voltage drop and power loss problems, this study proposes a network repair plan using ETAP 19.0.1 software to align consumer-side voltage and transformer loading with PLN standards. Repair measures include installing additional transformers in the low-voltage distribution network. Post-repair assessments indicate a voltage drop reduction of +2.5% or an increase of approximately 10 Volts at both substations.